Fluorescence properties of sol–gel materials doped with photosensitizers - Hołowacz, Iwona; Ulatowska-Jarża, Agnieszka; Wysocka, Katarzyna; Głuchowski, Paweł; Stręk, Wiesław; Podbielska, Halina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Sol–gel materials may found plenty of applications, e.g., as carriers for various substances, which can be exploited for sensing purposes or as drug releasing carriers. In this work, the fluorescence properties of two photosensitizers immobilized in silica based sol–gel materials were examined. The sol–gel materials were produced from silica precursor TEOS and 96% ethyl alcohol as solvent. Materials with various ratios R (solvent to precursor molar ratio) 5, 15, 20, 32, 40, and 50, were prepared. Photolon and protoporphyrine PPIX were used as dopants in concentrations 0.001%, 0.005%, 0.01% and 0.05%. The excitation wavelength from a blue laser was 415 nm. The highest luminescence was observed for the material prepared with R = 20, whereas for R = 5 it was the lowest one. The fluorescence quenching for highest photosensitizer concentration was observed, as well.
Optica Applicata, Vol. 38, 2008, nr 1, s. 49-56
Keywords: optyka; fluorescence; sol-gel material; photosensitizers